Penerapan Model Regresi Logistik Terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Sumatera Barat Tahun 2019 – 2021 - Fitri Rahmah Ul Hasanah; Mutia Yollanda (Journal of Science and Technology, 2022)
The human development index is an indicator that can measure the success of a region in developing human quality. The success of human development can be measured by how fundamental problems in society can be overcome, such as poverty, unemployment, and lack of access to public facilities. The increase in HDI in an area can be determined by several factors, including life expectancy (UHH) and the unemployment rate. One of the models that can be used to determine the factors that significantly affect the human development index is logistic regression, where logistic regression is an approach to making a predictive model in the form of the probability of a variable.The data used in this study are HDI, UHH, and unemployment rates in West Sumatra Province in 2019–2021. Based on the multicollinearity test, there is no relationship between UHH and the unemployment rate. This study was conducted to determine the factors that significantly affect the human development index of districts/cities in West Sumatra Province. Based on the results obtained, UHH has dramatically affected the HDI of districts/cities in West Sumatra Province over the last three years.